Kelayakan Finansial Agribisnis Persada Farm Bogor - Putri, Salsabilah Azzahra; Karyani, Tuti (Universitas Galuh, 2024)
The development of UMKM is currently quite rapid and has an effect on economic growth in Indonesia. West Java is known to be the province with the largest number of UMKM in Indonesia in 2022 with 6,664,548 units. Bogor is one of the areas in West Java that is strived for the development of UMKM with a total of 47,758 units in 2022. Persada Farm Bogor is one of the UMKM in Bogor City that was established in November 2020 and is engaged in agriculture, especially organic fruit and vegetable seeds. However, Persada Farm Bogor began to develop its business in processing products into finished products, namely kale juice. The development of Persada Farm Bogor, there is a need for a financial feasibility analysis to find out how the future prospects and how much added value is obtained from processing kale juice. This research uses a qualitative design with a case study approach. The financial feasibility analysis used Payback Period, Net Present Value, Internal Rate of Return, and Net B/C, while the value-added analysis used the Hayami method. The results showed that Persada Farm Bogor is not feasible to continue with the Payback Period value for 8 years and 8 months; Net Present Value Rp(158.778.250,8); undefined IRR; and net B/C of 0.3; while the added value obtained is Rp27,900 with an added value ratio of 27.9%.